1993
DOI: 10.1051/forest:19930301
|View full text |Cite
|
Sign up to set email alerts
|

Differences in drought resistance among 3 deciduous oak species grown in large boxes

Abstract: Summary — The purpose of this study was to explain large differences in growth and decline of the pedunculate oak (Ouercus robur L) and the sessile oak (Q petraea Liebl) observed in the forest as a result of drought. In addition, northern red oak (Q rubra L) was compared with the 2 indigenous oaks. The effects of controlled soil water deficits on growth and water relations of young plants of these 3 species grown in large boxes have been studied. The plants were old enough to have developed normal root s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 8 publications
4
33
2
8
Order By: Relevance
“…Here a combination of direct light, low precipitation due to interception, and root competition could have a drought effect. Quercus robur was reported as more sensitive to drought stress [37] compared to Q. petraea, but it seems more resistant than competing understory vegetation. This could be attributed to a deep root system, which can rapidly develop in a few years [13,17,23].…”
Section: Discussionmentioning
confidence: 99%
“…Here a combination of direct light, low precipitation due to interception, and root competition could have a drought effect. Quercus robur was reported as more sensitive to drought stress [37] compared to Q. petraea, but it seems more resistant than competing understory vegetation. This could be attributed to a deep root system, which can rapidly develop in a few years [13,17,23].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the oak decline which occurred in France following the severe 1976 drought showed that only Quercus robur was affected [14]. This could be explained by a higher sensitivity of Q. robur than Q. petraea to water deficits and a higher susceptibility to root pathogens [109,161,205].…”
Section: Species-specific and Genetic Effectsmentioning
confidence: 99%
“…Therefore, they tend to gain dominance over beech mainly at sites with more extreme soil moisture conditions [8]. Although, compared to the sessile oak, the pedunculate oak was found to have a larger water requirement [17] and to be more sensitive to drought stress [4,27], this species also occurs at sites with low water supply, e.g. on nutrient-poor sandy soils (Betulo-Quercetum roboris; [29]), or on plateaus and exposed slopes of well-drained limestone hills (xerothermic mixed oak forests; cf.…”
Section: Introductionmentioning
confidence: 99%